1988
DOI: 10.1093/ajcp/90.5.583
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of Three Different Methods for the Determination of Estrogen Receptors in Human Breast Cancer

Abstract: Forty-seven cases of breast cancer were analyzed for estrogen receptors (ERs) by three different techniques: (1) a biochemical assay using isoelectric focusing in polyacrylamide gel; (2) a monoclonal ER immunocytochemical assay (ERICA, Abbott Laboratories Diagnostics Division), and (3) a polyclonal antiestradiol immunohistochemical technique using formalin-fixed tissue. A high level of agreement (85%) was noted between the biochemical assay and ERICA. The ERICA-processed slides showed minimal background staini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
2

Year Published

1990
1990
2003
2003

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(5 citation statements)
references
References 0 publications
0
3
0
2
Order By: Relevance
“…Several evaluation systems have been proposed in the literature (9)(10)(11)(12) and involve positive cell population and staining intensity. To quantify the results by immunohistochemistry, the percentage of positive cells among 100 to 500 breast cancer cells should ideally be counted for the assessment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several evaluation systems have been proposed in the literature (9)(10)(11)(12) and involve positive cell population and staining intensity. To quantify the results by immunohistochemistry, the percentage of positive cells among 100 to 500 breast cancer cells should ideally be counted for the assessment.…”
Section: Discussionmentioning
confidence: 99%
“…Concordance rates between biochemical assays and immunohistochemistry were extensively studied in the 1980s to 1990s and ranged from 72.5% (7) to 95% (8) with frozen sections and from 67% (9) to 94% (10) with paraffin sections. Concordance rates between biochemical assays and immunohistochemistry were extensively studied in the 1980s to 1990s and ranged from 72.5% (7) to 95% (8) with frozen sections and from 67% (9) to 94% (10) with paraffin sections.…”
mentioning
confidence: 99%
“…Numerous studies have demonstrated the validity of the immunocytochemical methods to ascertain the levels of ER present in breast carcinoma (King et al, 1985;McCarty et al, 1985;Vlatkovic et al, 1987;Marchetti et al, 1987;Cudahy et al, 1988).…”
Section: Discussionmentioning
confidence: 99%
“…Μία διαφορετική προσέγγιση του θέματος έγινε σε περιορισμένο αριθμό μελετών και αφορά την ανίχνευση των ενδογενών στεροειδών ορμονών, οιστραδιόλη και προγεστερόνη, σε νεοπλασματικά κύτταρα και κυρίως σε καρκινώματα του μαστού (Mercer et al, 1980;Taylor et al, 1981;Shimizu et al, 1983;Katayama et al, 1984;Pascal et al, 1986;Cudahy et al, 1988;0'Keane et al, 1990). Οι μέθοδοι που χρησιμοποιήθηκαν ήταν ο ανοσοφθορισμός και η ανοσοϊστοχημεία.…”
Section: εισαγωγηunclassified